The discursive construction of lower-tracked students: Ideologies of meritocracy and the politics of education - Kate T. Anderson (Arizona State University, 2015)
This study considers the discursive construction of a particular type of student in Singapore - the lowest-tracked, Normal Technical (NT), secondary school student. Shaped by meritocratic policies, educational practices, and ideologies common to many late-modern societies, students in the NT track are institutionally and individually constructed through the results of high-stakes testing regimes and essentialist views of ability. This article extends an understanding of the NT student as a widely held, deficit construction in Singapore by considering its use as an ideological label in interpersonal and institutional discourse. I consider how school leaders' and government commentaries about NT students' abilities, opportunities, and supposed characteristics provide insights about the processes through which students are recruited into institutional categories of deficit and risk¾i.e. differentiated instruction, ascribed ability, and these processes' translation into educational structures and practice in the name of meritocracy. While the illustration of this phenomenon is uniquely Singaporean, implications include concerns about equity, constructions of ability, and ideologies of merit common to late modern society.